PECULIARITIES OF PE LESSONS' CARRYING OUT OF IMPROVING ORIENTATION IN THE CONDITIONS OF FSES REALISATION OF GENERAL EDUCATION - Viktor Pavlovich Lukyanenko; Natalia Vladimirovna Mukhanova; Alina Evgen'evna Volosnikova (Вестник Северо-Кавказского федерального университета)
There is a lot of information and a great experience in the development of programmes on organisation of PE studies with improving orientation in the domestic science and practice. However, results of mass inspections of schoolchildren's health state that traditional ways of improving influences by means ofphysical culture aren't effective enough. In the article there are original approaches to the organisation of PE lessons of improving orientation taking into consideration modern claims of FSES general education.